The Evolution of the Term Sulṭān in Early Islam - Kennedy, Hugh (Journal of Abbasid Studies, 2024)
This article discusses the use of the word sulṭān in Arabic political and historical discourse in the period before the term is regularly used as a title of rulership attached to an individual in the middle of the fifth/eleventh century. It describes four phases, sulṭān as abstract authority, sulṭān as state or administration, sulṭān as an informal descriptor of a powerful individual and sulṭān as a formal title used on coins. It argues that the changing uses are related to the changing nature of power and authority in the Muslim community.